In vitro activation of cryopreserved ovarian tissue: A single-arm meta-analysis and systematic review. (March 2021) - Wang, Wanxue; Todorov, Plamen; Isachenko, Evgenia; Rahimi, Gohar; Mallmann, Peter; Wang, Mengying; Isachenko, Vladimir
Highlights: Primordial follicles in premature ovarian failure (POF) patients are very difficult to be activated spontaneously. So mature oocytes are difficult to be obtained for in vitro fertilization in premature ovarian failure (POF) patients. For ovarian disorder patients, in vitro activation can be a promising option for fertility preservation. According to our results, drug-free in vitro activation of primordial follicles is a new potential treatment comparison with drug-induced activation. Abstract: Objective: Primordial follicles in premature ovarian failure (POF) patients are very difficult to be activated spontaneously, so that mature oocytes are difficult to be obtained for in vitro fertilization. The aim of our review is to analyze and to systematize the published data regarding effectiveness of different strategies for in vitro activation of cryopreserved ovarian tissue. Study design: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a review of the literature was performed for all relevant full-text articles published in PubMed in English. Meta-analysis conducted using STATA 14.0. The random-effects model was used to combine 8 study results because the examination of heterogeneity was minimal. Results: One hundred and seventy seven patients after in vitro activation treatment (IVA) of ovarian tissue had accumulatively 26 pregnancies through IVF or natural pregnancy and then produced 18 live births. The random-effects model showed that the total clinical pregnancy and baby born rates reported in 8 studies evidence about effectiveness of IVA. Conclusion: In vitro activation of primordial follicles as a new potential treatment for ovarian disorder patients, can be a promising option for fertility preservation. Drug-free activation of ovarian tissue in comparison with drug-included activation seemed to be more efficient.